ANALISIS KAPASITAS LENTUR BALOK BAJA DENGAN VARIASI PANJANG BENTANG - Nidiasari Nidiasari (Universitas Andalas, 2026)
This study aims to analyze the effect of length on the flexural capacity of WF section steel beams. Length variations are explained in terms of the unconfined length limits specified in AISC 360: short, intermediate, and long beams. The method used is numerical analysis, calculating the nominal flexural capacity (Mn) at various beam lengths using a 150×75 WF section. The results show that the maximum flexural capacity occurs at short beams, then decreases at intermediate beams due to inelastic lateral-torsional buckling, and decreases significantly at long beams due to elastic buckling. The ratio of the ultimate load capacity to the analytical load capacity at short beams is 0.83 and 1.12, intermediate beams 1.27 and 1.14, and long beams 1.44 and 1.7. In general, the theoretical and numerical capacities exhibit the same trend: a decrease in flexural capacity with increasing beam length.